2013
DOI: 10.1002/chem.201203365
|View full text |Cite
|
Sign up to set email alerts
|

A New Modular Phosphite‐Pyridine Ligand Library for Asymmetric Pd‐Catalyzed Allylic Substitution Reactions: A Study of the Key Pd‐π‐Allyl Intermediates

Abstract: A library of phosphite-pyridine ligands L1-L12 a-g has been successfully applied for the first time in the Pd-catalyzed allylic substitution reactions of several di- and trisubstituted substrates by using a wide range of C, N and O nucleophiles, among which are the little studied α-substituted malonates, β-diketones, and alkyl alcohols. The highly modular nature of this ligand library enables the substituents/configuration at the ligand backbone, and the substituents/configurations at the biaryl phosphite moie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 118 publications
0
25
0
Order By: Relevance
“…We next decided to take one further step in the design of new ligand libraries using phosphite–pyridines L36 – L47 12 and phosphite–amine L48 – L53 13 ligand libraries (Figure ), which incorporated the advantages of the heterodonor, the robustness of the pyridine/amine moieties, and the extra control provided by the flexibility of the chiral pocket through the presence of a biaryl phosphite group.…”
Section: Ligand Designmentioning
confidence: 99%
See 2 more Smart Citations
“…We next decided to take one further step in the design of new ligand libraries using phosphite–pyridines L36 – L47 12 and phosphite–amine L48 – L53 13 ligand libraries (Figure ), which incorporated the advantages of the heterodonor, the robustness of the pyridine/amine moieties, and the extra control provided by the flexibility of the chiral pocket through the presence of a biaryl phosphite group.…”
Section: Ligand Designmentioning
confidence: 99%
“…We next decided to synthesize and screen a library of 84 potential new phosphite–pyridine ligands ( L36 – L47c – g , j – k ; Figure ) 12a. These ligands incorporate the advantages of the heterodonor, the robustness of the pyridine moiety, and the extra control of the chiral pocket through the presence of biaryl phosphite groups.…”
Section: Application Of Phosphite‐based Ligands In Pd‐catalyzed Allylmentioning
confidence: 99%
See 1 more Smart Citation
“…To expand upon this research, it is of interest to incorporate other donating groups that can act as hemilabile ligands such as pyridyl groups . Similar heterodonor P,N ligand have been used successfully in Pd‐catalyzd Suzuiki–Miyayra coupling, asymmetric Pd‐catalyzed allylic alkylation reactions, Cu‐catalyzed asymmetric conjugate 1,4‐additions, and Ir‐ or Rh‐catalyzed alkene hydrogenations,, , but very few have been studied in Rh‐catalyzed hydroformylation reactions . These catalysts are more complicated than the mixed P‐donor/ether ligands that we previously studied because the pyridyl group is more likely to competitively bind to the catalytically active Rh I metal centers .…”
Section: Introductionmentioning
confidence: 99%
“…[4a, 6] Notably, in 2008, Chan and co-workers reported a palladium-catalyzed asymmetric allylic etherification of 1,3-diphenyl-2-propenyl acetate with alcohols in moderate to high yields (58-98 %) and good to excellent levels of enantioselectivity (83-96 %ee) by using the (S, p R)-FerroNPS ligand. [7] Meanwhile, the research groups of Hou, Ding, Fukuzawa, Du, and others [8] have also demonstrated independently that various bidentate phosphine or phosphite ligands associated with palladium centers afford chiral allylic ethers in moderate to good levels of enantioselectivity and diastereoselectivity. However, this useful process to provide chiral allylic ethers still needs substantial improvement in its level of enantioselectivity and chemical yield to be more practical.…”
mentioning
confidence: 99%